Effect of kinesio taping in myoelectric activity in patients with shoulder impingement - Dhein, William; Torre, Marcelo La; Loss, and Jefferson Fagundes (Manual Therapy, Posturology & Rehabilitation Journal, 2017)
Introduction: The complex shoulder joint is equipped with the greater joint mobility of the body, however, is commonly injured in repetitive, sport or occupational activities. Shoulder Impact Syndrome (SIS) is one of the most common injuries affecting the shoulder, thus causing limitations in its functionality. Several strategies have been used by physiotherapy for prevention and rehabilitation of SIS, one of them is the Kinesio Taping (KT). However, even with its abundant use there is still no clear evidence of its benefits. Objective: The aim of the study was to examine the effect of KT on myoelectric activity and the level of pain in patients with SIS. Method: Seven women with SIS participated, which performed the flexion and shoulder abduction up to 90° with and without KT. During the gestures, the pain level and surface electromyography data of the upper trapezoid, middle deltoid and anterior serratus were acquired. The treatment of the electromyography data was performed in the BIOMEC-SAS software and presented as percentage values of the maximum voluntary contraction. To compare the myoelectric activity and pain levels, it was performed, respectively, one way ANOVA and the Wilcoxon test (α <0.05). Results: Pain reductions were observed and myoelectric activity of upper trapezius (46.0±34.4% MVIC to 35.6 ± 19.5% MVIC) and middle deltoid (39.0±11.5% MVIC to 35.2±12.5% MVIC) in motion abduction use of KT. No changes were observed in the signs during flexion movement. Conclusion: Finally, the KT generated a reduction in the level of pain and myoelectric activity of the middle deltoid and upper trapezius in the movement of abduction in patients with SIS.